Mosque-Based Zakat Collection in Maximizing Zakat Potential in Yogyakarta - Syayyidah Maftuhatul Jannah; Hasan Al-Banna (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: Indonesia as the most populous Muslim country has huge potential of zakat collection. However, the zakat collection never meets its potential. Hence, the need for localization is critical in order to maximize the zakat collection.Objective Study: this paper attempt to develop the mosque-based zakat collection in order to maximize the potential of zakat.Methodology: based on literature review and empirical investigation, self-administered questionnaire is developed to collect the data. Hence, we use Partial Least Square Structural Equation Modelling (PLS-SEM) to analyze the data. The sample of this research is the mosque management (takmir masjid).Findings: This study found that service quality of zakat institution significantly influences the intention to distribute the zakat. While zakat distribution influences insignificantly to the intention to distribute the zakat. Meanwhile, trust moderates between zakat distribution from zakat institution to intention to distribute the zakat